2014
DOI: 10.1175/wcas-d-13-00026.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Previous Disaster Experience and Sociodemographics on Protective Behaviors during Two Successive Tornado Events

Abstract: The role of previous disaster experience

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…Rapid‐onset severe weather generates problems with the general public not heeding official warning signals and evacuation notices (Dow & Cutter, 1998; Silver & Andrey, 2014). Various factors feed into this tendency to ignore warnings.…”
Section: Incompatibility Generated By Misperceptions About the Measurmentioning
confidence: 99%
“…Rapid‐onset severe weather generates problems with the general public not heeding official warning signals and evacuation notices (Dow & Cutter, 1998; Silver & Andrey, 2014). Various factors feed into this tendency to ignore warnings.…”
Section: Incompatibility Generated By Misperceptions About the Measurmentioning
confidence: 99%
“…Personal experience plays an important role in individual risk perceptions of future events as well as preparedness and mitigation behaviors, although the effect of experience is likely to be contingent on situation-specific aspects of the event (e.g., type, magnitude, distance), individual factors (e.g., knowledge, values, attitudes, emotions) and social context (e.g., media reports, peer influences, culture) (McGee et al 2009;Zaalberg et al 2009;Wachinger et al 2013;Silver and Andrey 2014). Moreover, the effect of experience on perceptions and attitudes can create "windows of opportunity" for policy change (Tierney 2007;McGee et al 2009).…”
mentioning
confidence: 99%
“…It is generally cited as a positive influence on risk perception . For instance, two case studies found enhanced risk perception and protective action for the second of two successive tornado events striking cities . Some studies consider differences in direct experience between those who suffered personal loss (e.g., property damage or injury) and those who did not.…”
Section: Literature Reviewmentioning
confidence: 99%